A Review of IoT Security Issues in Smart City Systems - Sameer, Ahmed; Chitra, K. (INTI International University, 2025)
The rapid development of smart cities relies heavily on interconnected IoT devices, intelligent communication infrastructures, and emerging technologies such as artificial intelligence and blockchain. While these advancements enhance urban efficiency, they also introduce significant security challenges that threaten data integrity, privacy, and system resilience. This review critically examines the key IoT security issues encountered in smart city ecosystems, including vulnerabilities in device authentication, insecure communication protocols, data leakage, and weak access control mechanisms. The objective of this review is to consolidate existing research on IoT-related security threats within smart city environments and evaluate how modern technologies are being used to mitigate these issues. The paper identifies key research gaps such as the lack of unified security frameworks, inadequate real-time threat detection, and limited scalability of existing solutions. Future directions are proposed, emphasizing the integration of AI-driven threat analytics, blockchain-based trust models, and standardized security architectures to strengthen the security posture of next-generation smart cities.